An Instructional Teaching- Learning Design Based On Integrative Approach And Its Impact On The Pivotal Thinking And Achievement Motivation Among Students Of The Fourth Stage In The College Of Basic Education - Rabea Husin, D. Ali (Opción, 2019)
The aim of this research is to identify an educational design based on the in- tegrative approach and its impact on the pivotal thinking and motivation of achievement among the students of the fourth stage in the College of Basic Ed- ucation of the University of Anbar. To achieve this, the researcher followed the experimental approach, where the research sample consisted of (66) students from the fourth stage, distributed into two experimental and control groups and randomly, and the research tool consisted of a test built by the researcher to measure the pivotal thinking of the research sample and the test consists of (35) A paragraph of the type of multiple choice has been verified honesty and consistency and conduct statistical analyzes of the test paragraphs, and the researcher prepared a measure of motivation of achievement to measure the extent of their motivation towards the material and be (20) paragraph.